2010
DOI: 10.1108/14678041011026865
|View full text |Cite
|
Sign up to set email alerts
|

Usage patterns in a Greek academic library catalogue

Abstract: PurposeThe purpose of this paper is to focus on searches made by the patrons of the Library of the ATEI of Thessaloniki using its online catalogue during the spring semester of the academic year 2007/2008. A previous study had revealed that patrons experienced difficulties while searching the OPAC and did not make the most of the system's capabilities. As a result, the library re‐examined specific aspects of its services and its user education programnes, and updated its software. The present research was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Furthermore, the results point out that, although the first steps can be made through an ISO 9001:2000 certification, further issues need to be addressed in order to seek the best solutions for quality management in academic libraries in Greece. These may include the cooperation and enhancement of the interlibrary loan network in Greece (Katsirikou, 2004;Tsimpoglou, 2004), the study of user patterns in digital services of academic libraries (Malliari et al, 2010) and the management of repositories and open access material (Georgiou and Papadatou, 2010), etc.…”
Section: Quality and Innovation For Greek Academic Librariesmentioning
confidence: 99%
“…Furthermore, the results point out that, although the first steps can be made through an ISO 9001:2000 certification, further issues need to be addressed in order to seek the best solutions for quality management in academic libraries in Greece. These may include the cooperation and enhancement of the interlibrary loan network in Greece (Katsirikou, 2004;Tsimpoglou, 2004), the study of user patterns in digital services of academic libraries (Malliari et al, 2010) and the management of repositories and open access material (Georgiou and Papadatou, 2010), etc.…”
Section: Quality and Innovation For Greek Academic Librariesmentioning
confidence: 99%
“…There are various studies in which two sets of transaction log data were used to understand the usability and user-friendliness of search interfaces, one before any modifications in the interfaces and the other after the modifications. Earlier data for interfaces without modifications reveal that the users are not fully compatible with the basic search techniques, while the later show statistically significant differences in the results revealing that the modified interfaces are more compatible and userfriendly as the users show positive effect in their search attitude while working after the interfaces are being modified [23][24][25] . Designers are more likely to be successful in designing interfaces if they spend time with users, observing how they work…”
Section: Literature Reviewmentioning
confidence: 98%
“…Kani‐Zabihi et al (2008) reported that regardless of user's information technology backgrounds, their expectations of the functionality of OPACs were the same because users continued to expect OPACs also to facilitate easier ways to achieve their tasks. Malliari et al (2010), on the other hand, determined the impact of changes made to OPACs at the Alexander Technological Educational Institution of Thessaloniki, Greece. Their study highlighted the fact that the changes had a positive impact on the users and their attitude towards such usage.…”
Section: Literature Reviewmentioning
confidence: 99%